Peran Penyiar Kelana Kota Rasika Sebagai Gatekeeper Dalam Penyampaian Informasi Lalu Lintas Pada Masa Lebaran Th 2022 - Triyono, Oktaviana Anggraeni; Sari, Dewi Kartika; Herwandito, Seto (Innovative: Journal Of Social Science Research, 2024)
In 2020 the whole world was hit by the Covid-19 pandemic which caused all activities to be restricted, with the emergence of the Covid-19 virus causing major changes in human life. The Indonesia government is also implementing a PPKM system where all activities are very limited, so that in 2020 the entire community will not be able to go home. As time went by in 2022, the government allowed people to be able to carry out homecoming activities, so that 2022 was the peak of the homecoming flow for the Eid holiday. All people flocked to return to their hometowns, at the same time all people also needed information about the streets. Radio Rasika is a radio station that broadcast information about road traffic. Radio Rasika has a permanent program, namely Kelana Kota, Kelana Kota Radio Rasika broadcasters also have a role as gatekeepers, they present programs with their own characteristics. Therefore, this research aims to determine the role of Kelana Kota broadcasters as gatekeepers in conveying traffic information for the 2022 Eid holiday. In this research, researchers use gatekeeping theory. This research is included in the type of research with descriptive methods. Researchers carried out data collection techniques through in-depth interviews and direct observation on Radio Rasika Ungaran. This research also determines the techniques and methods of Kelana Kota Radio Rasika broadcasters is managing the information received from listeners.